The Effect of Using Knee Support on Reducing Knee Pain in Elderly Cyclists - Suprayogi, Dody; Zubaidi, Alfan; Widagdo , F.A. Hendy Setyo (Journal of Prosthetics Orthotics and Science Technology, 2024)
Background: Knee pain during cycling can arise due to the repetitive movements involved in the activity. Overuse injuries, also termed repetitive strain injuries, denote damage and discomfort resulting from repetitive and excessive motions. Such injuries typically affect muscles, tendons, and bones. This pain may persist, particularly during strenuous activities like exercise. Knee support represents a common orthotic tool utilized to alleviate knee pain. Aims: The aim of this study is to ascertain whether the use of knee support has an effect on reducing the degree of knee pain in elderly cyclists. Methods: The research employs a quasi-experimental design with pre- and post-test assessments. Twenty-five subjects were selected using purposive sampling techniques based on predefined inclusion and exclusion criteria. Results: The analysis employed the Wilcoxon test, yielding a p-value of (0.001). Since the p-value is ?0.05, it can be inferred that the utilization of knee support effectively diminishes the degree of knee pain in elderly cyclists. Conclusion: This study demonstrates the efficacy of knee support in reducing knee pain among elderly cyclists. Hence, it is advisable for elderly cyclists to utilize knee braces while cycling.